2005
DOI: 10.1590/s1679-62252005000100006
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetical and morphological features reveal significant differences among Venezuelan and Brazilian samples of Mugil curema (Teleostei: Mugilidae)

Abstract: Karyotype of M. curema from the Gulf of Mexico and Brazil have been reported as possessing chromosome complement with 2n=28 and FN=48, whereas specimens from Venezuela has been reported as possessing a diploid number 2n=24 and a conserved FN (48). Although at first sight this variation suggests the presence of a chromosomal intraspecific (interpopulational) variability, the possibility that we are dealing with two different species was examined. This work revisit the karyotypes of M. curema from Venezuela and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 8 publications
1
27
0
5
Order By: Relevance
“…The latter cytotypes have been found in specimens of Mugil curema from Louisiana and Brasil (2n = 28, NF = 48;LeGrande and Fitzsimons 1976;Nirchio et al 2005) and from Venezuela (2n = 24, NF = 48; Nirchio and Cequea 1998;Nirchio et al 2007, among others). They were originally interpreted (LeGrande and Fitzsimons 1976) to be due to extensive Robertsonian fusions which occurred in an ancestral group with an all-acrocentric chromosome complement (cytotype A) similar to that of M. cephalus.…”
Section: Introductionmentioning
confidence: 81%
“…The latter cytotypes have been found in specimens of Mugil curema from Louisiana and Brasil (2n = 28, NF = 48;LeGrande and Fitzsimons 1976;Nirchio et al 2005) and from Venezuela (2n = 24, NF = 48; Nirchio and Cequea 1998;Nirchio et al 2007, among others). They were originally interpreted (LeGrande and Fitzsimons 1976) to be due to extensive Robertsonian fusions which occurred in an ancestral group with an all-acrocentric chromosome complement (cytotype A) similar to that of M. cephalus.…”
Section: Introductionmentioning
confidence: 81%
“…Karyological information about the Mugilidae shows that NORs are located: on the telomeric region of the long arm of acrocen-tric chromosome pair N°1 in M. cephalus (Rossi et al, 1996), M. platanus (Jordao et al, 1992), and M. liza (Nirchio et al, 2001); on the telomeric region of the long arm of the metacentric chromosome pair N°1 in M. curema from Venezuela (Nirchio et al, 2001); on the telomeric region of the short arm of the subtelocentric chromosome pair N°11 in M. curema from Brazil (Nirchio et al, 2005); and on the short arm of the unique submetacentric chromosome pair (N°24) of Liza aurata, L. ramada, L. saliens and Chelon labrosus (Rossi et al, 1997;Gornung et al, 2001). In Oedalechilus labeo, one pair of NORs that are strikingly different in size is located on the short arms of the only subtelocentric pair (N°9); although there can be an additional, though inactive NOR, in the chromosome complement (Rossi et al, 2000).…”
Section: Cytogeneticmentioning
confidence: 99%
“…Recent cytogenetic studies carried out on several Mugilidae species from Venezuela (reviewed in Sola et al, 2007Sola et al, , 2008 have provided information regarding several interesting systematic and cytotaxonomic issues within the family. For example, the cytogenetic studies made it possible to establish that Mugil rubrioculus is a separate species from M. curema (Nirchio et al, 2003 and also indicated the likely existence of a species complex within M. curema (Nirchio & Cequea, 1998;Nirchio et al, 2005a). Moreover, the localization of major and minor ribosomal genes revealed that the 48 uniarmed chromosome karyotype, displayed by all the Mugilidae species, with the exception of M. curema, is much more differentiated than the macromorphology of chromosomes would suggest (Sola et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%